Main Symptom that Led to Medical Evaluation and Diagnosis of Vestibular Schwannoma and Patient-Reported Tumor Size: Cross-sectional Study in 1,304 Patients - Peris-Celda, Maria; Graffeo, Christopher S.; Perry, Avital; Kerezoudis, Panagiotis; Tombers, Nicole M.; Carlson, Matthew L.; Link, Michael J. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objectives Although vestibular schwannomas (VS) are known to cause cranial nerve deficits, cerebellar symptoms, and hydrocephalus, the role of these symptoms as the key driver of presentation from the patient's perspective has not been described. Our objective was to survey a large, retrospective VS cohort to document the patient-reported principal initial symptom, and self-reported tumor size, and to study trends in VS patient presentation.Methods Patients diagnosed with VS at our tertiary referral center and belonging to the Acoustic Neuroma Association (ANA) answered a questionnaire between 2015 and 2017. Demographic data, self-reported tumor size, and symptomatology were analyzed.Results 1,304 patients completed the questionnaire. Tumors were diagnosed from 1966 to 2017 at a mean 51.8 years (range: 8–86 years); 66% were female, and 1.1% had confirmed neurofibromatosis type 2 (NF2). Tumor size was reported using a 6-point scale: 0 to 1 cm (22.9%), 1 to 2 cm (28.7%), 2 to 3 cm (20.5%), 3 to 4 cm (10%), greater than 4 cm (7.2%), and unknown (10.6%). Hearing loss was the most common symptom that led to diagnosis (51.5%), followed by dizziness (17%), tinnitus (11.2%), and incidental diagnosis (10.2%); a fraction that has increased significantly in the last decade (p = 0.022). Larger tumors and NF2 were significantly associated with young age (p < 0.001).Conclusion Our large-scale questionnaire-driven review of 1,304 patients confirms that VS presentations are stereotypical, with most individuals recalling hearing loss, dizziness, or tinnitus as their chief complaint. Many tumors were incidentally diagnosed; an expanding population, attributable to increased access to magnetic resonance imaging (MRI). Large tumors were significantly more prevalent among younger patients at diagnosis, excluding NF2 patients, suggesting a more aggressive tumor biology that remains incompletely understood.
Keywords: vestibular schwannoma; hearing loss; dizziness; symptoms at presentation; acoustic neuroma